Coloring of Cervical Cancer’s Ct Images to Localize Cervical Cancer - Erlinda Ratnasari Putri; Amar Vijai Nasrulloh; Arfan Eko Fahrudin (Institute of Advanced Engineering and Science, 2015)
Cervical cancer is the most common gynecologic cancer in women. Cervical cancer and the normal cervix usually have similar attenuations on CT images which are obtained. The normal cervix and the tumour cannot be distinguished on normal CT images. CT image of cervical cancer is used by the experts for the analysis of diseases. In this research study, CT image of cervical cancer is done with process of image segmentation and coloring. The process of image segmentation is done after the image sharpening process and the determination of cervical cancer’s area. Fuzzy C-Means is used as the algorithm for image segmentation. The colors of image segmentation result are changed by program module. The result is the colors of image segmentation uniform with the other results. The image is overlayed with image result of image sharpening process. Coloring image purposes are to distinguish between cervical cancer’s area and normal organ and to localize the existence of cervical cancer. Based on the doctor’s observation, the empirical rate of testing 20 samples on the program is 100%.